Paediatric hypertension for the primary care provider: What you need to know - Saini, Priya (Paediatr Child Health, 2020)
The prevalence of hypertension has increased in the paediatric and adolescent populations, and is estimated between 1% and 2% in Canada. Paediatric and adolescent hypertension differs from adult hypertension in many ways, and primary care providers may not be up to date with current guidelines and recommendations. Recently, the American Academy of Pediatrics updated and published guidelines on the diagnosis, evaluation, and management of hypertension in children and adolescents. This paper summarizes these new guidelines in addition to the existing Canadian guidelines in a simple four-step approach, catered to a primary care setting, detailing the diagnosis, evaluation, workup, and management of hypertension in children and adolescents.